Shared patterns of population genomic variation and phenotypic response across rapid range expansions in two invasive lady beetle species - Angela G. Jones; John J. Obrycki; Arun Sethuraman; David W. Weisrock (Biological Control)
Non-native lady beetle species have often been introduced, with variable success, into North America for biological control of aphids, scales, whiteflies, and other agricultural pests. Two predatory lady beetle species, Propylea quatuordecimpunctata and Hippodamia variegata, both originating from Eurasia, were first discovered near Montreal, Quebec, in North America in 1968 and 1984, respectively, and have since expanded into northeastern North America and the midwestern United States. In this study, we estimate the range-wide population structure, establishment and range-expansion, and recent evolutionary history of these lady beetle species using reduced-representation genotyping-by-sequencing via ddRADseq. In addition, we quantified the responses to a key abiotic factor, photoperiod, that regulates adult reproductive diapause in these two species and may influence their geographical range in North America. Our analyses detect: (1) non-significant genetic differentiation and divergence among North American populations that likely originated from a single accidental introduction, (2) evidence of reduced contemporary gene flow within the continental US, and (3) minor phenotypic differences in diapause induction between populations of the two species from the same location.